Pricing and assembly rate decisions for a prefabricated construction supply chain under subsidy policies - Jiang, Wen; Qi, Xian (PLOS ONE, 2022)
Prefabricated construction has attracted worldwide concern and promotion due to its environmental friendliness, high quality, and high efficiency. In China, the application of prefabricated construction still lags due to its high cost. To improve prefabricated construction development, the Chinese government and provinces have launched subsidy policies for different objects that offer subsidies to the assembler, the manufacturer, or consumers. Subsidy policies for different subsidy objects have different impacts on the manufacturer wholesale price and assembler retail price and assembly rate and make their decisions more complicated. Therefore, this study uses game theory and builds three models to analyze the effects of government subsidies on manufacturer pricing, assembler pricing, assembly rate decisions, and profit. We find that government subsidy policies can bring more profit to prefabricated construction enterprises, reduce their costs, and benefit the promotion of prefabricated construction. Through comparison and numerical analysis, we also find that when the government subsidizes enterprises more, it is better to subsidize the assembler, because it is good for all three parties. First, consumers can obtain a lower retail price. Second, enterprises can obtain more profits. Finally, for the government, this approach can increase the demand for prefabricated construction and increase the assembly rate, which is conducive to the promotion of prefabricated construction. When the government subsidizes customers more, it is better for the assembler and the manufacturer to subsidize customers, because they can obtain more profits. It is better for the government and customers to subsidize the assembler or the manufacture, because consumers can get the lower retail price. Although the assembly rate and enterprises’ profits are not optimal, they have also been improved. In addition, when the government directly subsidizes enterprises, the enterprises will actively cooperate with the subsidy policy and are more willing to adopt prefabricated construction. This approach will benefit the promotion of prefabricated construction.